1985
DOI: 10.1002/jcp.1041220315
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of K562 cell transferrin receptors by exogenous iron

Abstract: Single-cell analysis of K562 human erythroleukemia cells by flow cytometry was used to demonstrate the specific role of iron in regulating transferrin receptors (TfRs) and to establish that TfR expression does not necessarily correlate with growth rate. Exogenous iron concentration in culture was manipulated by supplementing the medium with sera having different iron concentrations over the range 0.6 to 5.4 micrograms/ml, by the addition of iron in the form of FeCl3, iron-saturated serum, or diferric transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Relative size, estimated by LALS (n = 3) vitro, the observed decreases cannot be attributed to depletion of these components from the culture medium, for Tf is recycled to the cell after it is separated from the iron it carries (11,131 and iron deficiency reversibly induces TfR expression in K562 cells (24). Hence, decreased T f R density appears to be an early single-cell marker for changes in cell growth rate.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Relative size, estimated by LALS (n = 3) vitro, the observed decreases cannot be attributed to depletion of these components from the culture medium, for Tf is recycled to the cell after it is separated from the iron it carries (11,131 and iron deficiency reversibly induces TfR expression in K562 cells (24). Hence, decreased T f R density appears to be an early single-cell marker for changes in cell growth rate.…”
Section: Discussionmentioning
confidence: 95%
“…A third possibility, that iron uptake is regulated solely by differential rates of internalization of the W-receptor complex and not by changes in the number of surface receptors, does not explain decreased receptor expression with decreasing growth rate (Fig. 7) or the reversible induction of TfRs on K562 cells grown under conditions of iron deficiency (24). However, some of these questions can be addressed directly by real-time kinetic analysis of fluorescent Tf uptake as a function of DNA content.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Deferoxamine is the preferred iron chelator, because it enters the cell (7), whereas DTPA is restricted to extracellular chelation (21). Deferoxamine depletes the intracellular iron pool as evidenced by (i) a shift in transferrin receptor synthesis and display (21,23), (ii) depletion of intracellular ferritin iron (7,8), and (iii) the decrease in the iron-regulated rate of ferritin synthesis (24).…”
Section: Imentioning
confidence: 99%
“…It is well established that the principal mechanism for modulating cellular iron uptake is by regulation of ex pression of the Tf receptor [25][26][27][28][29], In the present inves tigation, it was shown that the rate of iron uptake by breast cancer cells was higher as compared to breast epi thelial cells, in spite of the identical rate of proliferation and lower number of Tf receptors. These results indicate that the number of Tf receptors on the cell surface was not in direct correlation with the cellular iron incorpora tion.…”
Section: Discussionmentioning
confidence: 52%